2003
DOI: 10.2169/internalmedicine.42.117
|View full text |Cite
|
Sign up to set email alerts
|

Intravascular Large B Cell Lymphoma Diagnosed by Senile Angioma Biopsy.

Abstract: An 82-year-old man without notable medical history was admitted to our hospital following subacute deterioration of apettite, disorientation and strange behavior. There was spasticity of the right extremities without weakness. LDHand serum soluble IL2 receptor antibody levels were elevated, and as well as the protein level and IgG levels in the cerebrospinal fluid. CT scanning of the brain revealed a lesion at the left corona radiata. The patient's level of consciousness was worsening, and follow-up study of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 7 publications
(9 reference statements)
1
15
0
1
Order By: Relevance
“…Colonization of preexistent cutaneous hemangiomas, similar to that observed in our patient, has been described in 2 other cases [15][16][17]. Although this is an exceptional Cerroni phenomenon, given the rarity of intravascular large B-cell lymphoma it seems to represent rather a peculiar clinicopathologic presentation of this type of lymphoma than just a chance association.…”
supporting
confidence: 86%
“…Colonization of preexistent cutaneous hemangiomas, similar to that observed in our patient, has been described in 2 other cases [15][16][17]. Although this is an exceptional Cerroni phenomenon, given the rarity of intravascular large B-cell lymphoma it seems to represent rather a peculiar clinicopathologic presentation of this type of lymphoma than just a chance association.…”
supporting
confidence: 86%
“…However, small red papules indicative of senile angioma, as in this case, are rare 7. To our knowledge, only four cases of senile angioma-like eruptions or haemangiomatous lesions in IVLBCL have been reported in the English language literature 3 , 810. These four cases, along with the case reported here, are summarised in table 1.…”
Section: Discussionmentioning
confidence: 62%
“…It primarily affects the skin and nervous system and sometimes lung and adrenal gland; however, it rarely involves the bone marrow, lymph nodes, liver and spleen, which are common targets of other lymphomas 2. IVLBCL is clinically aggressive and usually fatal, but the disease is quite difficult to diagnose while the patient is alive because the clinical symptoms, laboratory tests and biopsy specimens of bone marrow or peripheral blood smears usually show no specific findings 13. Here, we report a case of IVLBCL that could be diagnosed by a skin biopsy of a senile angioma-like eruption at an early stage and responded well to chemotherapy.…”
Section: Introductionmentioning
confidence: 93%
“…Satoh et al (11) showed the clinical usefulness of performing biopsy of cherry haemangiomas for the diagnosis of intravascular lymphoma (IVL). IVL is a rare subtype of extranodal diffuse large B-cell lymphoma with an aggressive clinical course, characterized histologically by predominant proliferation of lymphoma cells within the blood vessel.…”
Section: Discussionmentioning
confidence: 99%